2023
DOI: 10.1002/aisy.202200400
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Flexible and Programmable Negative Stiffness Mechanical Metamaterials

Abstract: Energy‐absorbing materials are widely used under certain high‐frequency scenarios, such as cargo packaging or sport protection. Though negative stiffness mechanical metamaterials have many distinctive advantages, fairly low strength and poor specific energy absorption unfortunately limit their present industrial applications. Inspired by the excellent cushioning performance of the paw pads of mammals, a novel flexible energy‐absorbing negative stiffness mechanical metamaterial is proposed herein. Results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…In these previous studies on the mechanics and design of bi-stable mechanical materials, it was shown that these metamaterials have interesting properties in terms of energy absorption [22,60] and impact protection [61,62]. More recent studies have focused on the tuning of the BG and control of wave propagation in systems composed of bi-stable elements, including deformation of the metamaterials to achieve tuning of the BG by regulating the air pressure [63], controlling the temperature change [64,65], and applying an external load [66], all of which have shown some success.…”
Section: Introductionmentioning
confidence: 99%
“…In these previous studies on the mechanics and design of bi-stable mechanical materials, it was shown that these metamaterials have interesting properties in terms of energy absorption [22,60] and impact protection [61,62]. More recent studies have focused on the tuning of the BG and control of wave propagation in systems composed of bi-stable elements, including deformation of the metamaterials to achieve tuning of the BG by regulating the air pressure [63], controlling the temperature change [64,65], and applying an external load [66], all of which have shown some success.…”
Section: Introductionmentioning
confidence: 99%
“…Metamaterials with tunable mechanical properties [11][12][13][14] , in particular having a rich dynamical behavior [15][16][17][18][19][20][21][22] or exhibiting non-reciprocity 23,24 , are extremely attractive for numerous applications, such as control of the propagation of acoustic and elastic waves [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] . Beyond the homogenization limit, the idea of dynamic shear, bulk, or mass density is commonly used and accepted for waves 41 .…”
Section: Introductionmentioning
confidence: 99%
“…This property signifies a material's ability to absorb and dissipate energy during impact or vibration exposure. Notably, superior energy absorption attributes directly translate to enhanced cushioning performance (Ganesh et al, 2022;Tan et al, 2023). Nonetheless, the viscosity of a material exerts a notable influence on its energy absorption properties (Huang et al, 2021;Saed et al, 2021).…”
Section: Introductionmentioning
confidence: 99%